A comparison of breastfeeding among Han, Uygur and other ethnic groups in Xinjiang, PR China - Shi Lin; Nazi Guli; Binns Colin; Xu Fenglian; Zhao Yun; Lee Andy (BMC, 2006)
Abstract Background Breastfeeding is an important factor in infant health and there have been no previous studies of breastfeeding practices in the different ethnic groups of this region of China. We aimed to compare breastfeeding rates and duration between Han, Uygur and other ethnic groups living in Xinjiang, PR China. Methods A longitudinal study of infant feeding practices was undertaken using a sample that included different ethnic groups. Mothers were randomly recruited and interviewed in hospitals and after discharge were contacted in person or by telephone at approximately monthly intervals to obtain details of infant feeding practices. Setting: Xinjiang Uygur Autonomous Region, PR China. Subjects: A total of1219 mothers (578 Han, 360 Uygur and 281 'other minority' mothers) who delivered babies during 2003 and 2004 were interviewed in five hospitals or institutes located in both urban and rural areas. Results 'Any breastfeeding' rates in Han, Uygur and 'other minority' groups at discharge were 88.5 %, 94.3 % and 97.1 % respectively, and at six months 76.7 %, 54.7 % and 87.6 % respectively. While 'exclusive breastfeeding' rates in the Han, Uygur and 'other minority' groups at discharge were 78.0 %, 34.5 % and 83.1 % respectively, at six months they had fallen to 4.8 %, 0.4 % and 16.8 % respectively. The median duration of 'Exclusive breastfeeding' of Han, Uygur and 'other minority' babies were 1.5, 0.1 and 2.5 months respectively. The Uygur babies were least likely to be 'exclusive breastfed'. Conclusion Uygur babies were least likely to be 'exclusive breastfed' and continued to 'any breastfeed' at six month. The 'any breastfeeding' rates in the Han group were lower in the first four months. An education program focused on breastfeeding continuation and exclusive breastfeeding is necessary in Xinjiang, especially for Uygur and Han ethnic groups.